1977
DOI: 10.1021/bi00645a014
|View full text |Cite
|
Sign up to set email alerts
|

Deuteron nuclear magnetic resonance studies of phase equilibriums in a lecithin-water system

Abstract: Water deuteron NMR spectra have been studied for the system dipalmitoyllecithin (DPL)-heavy water (D2O) at different compositions and temperatures. From an analysis of the spectra in terms of quadrupole splittings, a phase diagram has been constructed for the temperature range 25-60 degrees C and the composition range 4-15 mol of D2O/mol of DPL. Evidence is given that the "pretransition" observed by differential scanning calorimetry is caused by a crossing of a three-phase line. Strong support for a specific h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
108
0
3

Year Published

1981
1981
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(121 citation statements)
references
References 16 publications
(18 reference statements)
10
108
0
3
Order By: Relevance
“…This additional motional narrowing of the spectra near the chain melting phase transition of phospholipids was first reported by Salsbury et al (1972), and has since been studied by several authors (Ulmius et al 1977;Pope et al 1981;Strenk et al 1985;Hawton and Doane 1987). Similar effects have been seen in the gel-fluid phase transition of bilayer forming soaps (Abdolall et al 1977(Abdolall et al , 1978.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…This additional motional narrowing of the spectra near the chain melting phase transition of phospholipids was first reported by Salsbury et al (1972), and has since been studied by several authors (Ulmius et al 1977;Pope et al 1981;Strenk et al 1985;Hawton and Doane 1987). Similar effects have been seen in the gel-fluid phase transition of bilayer forming soaps (Abdolall et al 1977(Abdolall et al , 1978.…”
Section: Introductionsupporting
confidence: 68%
“…Salsbury et al (1972) suggested that changes in the water structure around the headgroup caused changes in the water mobility, without detailing what changes were responsible or why it occurred over a wide temperature range. Ulmius et al (1977) suggested that the effect may be due to diffusion along the ripples in the ripple phase which is intermediate between the gel and fluid phases in PC. Strenk et al (1985) used this idea to make estimates of the ripple periods from their measurements, using a non-zero asymmetry parameter to model the data.…”
Section: Introductionmentioning
confidence: 99%
“…From the phase diagram of the DPPC/water system, which is by now well established (e.g. Chapman et al 1967;Tardieu et al 1973;Janiak et al 1976Janiak et al , 1979Ulmius et al 1977) we infer that this composition should be in the biologically interesting liquid-crystalline phase (L~) for temperatures above the main phase transition at 315 K. a For the tail group dihedrals CH 2 -CH 2 -CH 2 -CHn we used the Ryckaert-Bellemans potential Bellemans 1975, 1978) b Normal dihedral potential: V(cp)= C (1 +cos(n q~-b)) c Improper dihedral potential: V(a) = 1/2 C (a_%)z Charges were derived from the quantum mechanical charge distribution. In the run with the reduced charges all the above partial atomic charges, except for the water, were reduced by a factor of 2 In order to set up an initial configuration for the system it is imperative to know both the surface area per headgroup of a lecithin (S) and the bilayer repeat distance (d) at the simulation temperature, which was set to 335 K. Various experiments (Chapman et al 1967;Reiss-Husson 1967;Phillips et al 1968;Levine and Wilkins 1971;Janiak et al 1976Janiak et al , 1979Biildt et al 1979) on lecithin systems under similar conditions provide a substantial range of values.…”
Section: Setup Of the Starting Configurationmentioning
confidence: 99%
“…2 H NMR of deuter-wavelength 1.542 Å was provided by a Seifert ID-300 Xray generator, operating at 50 kV and 40 mA. A 10-mm thick ated water can be conveniently used to study the phase equilibria of amphiphile-water systems (7,12,(15)(16)(17).…”
mentioning
confidence: 99%